Composição, distribuição estacional e uso de habitats em uma assembléia de anuros de afloramentos rochosos do semiárido brasileiro - Castro, Déborah Praciano de (2012)
Comprehending the levels of abundance and spatial distribution of species in their habitats is a central theme in ecology. Spatial patterns of species distribution, combined with environmental factors such as seasonality, provide important information to unravel the forces that maintain and structure biological diversity. Anuran amphibians are great starting points for studying ecological assemblages, and the fact that they are highly dependent on environmental variables makes the study of these animals even more interesting. Based on these assumptions, we present the main objective of this study to provide information on richness, diversity, reproductive modes and use of microhabitats by an assembly of anurans of rocky outcrops in Brazilian semi-arid region. The field work was conducted from July 2010 to July 2011 in monthly collections lasting three days in the city of Itapipoca, Ceará, in the area called Paleontological Site Lajinha. Methodologies were used in an active search and occasional encounters at breeding sites to demonstrate the richness, frequency and abundance of species. We find 19 anuran species, distributed in 13 genera from five different families, most of them with broad occurrence in Brazil and Latin America. The assemblage had a greater number of species of the Leptodactylidae family, and the most abundant species were Pseudopaludicola mystacalis, Pleurodema diplolister, Physalaemus albifrons and Scinax xsignatus. All species of the assemblage made differential use of microhabitats as a way to resist the dry season, and showed reproductive events restricted to the rainy season. Most patterns found were already expected for the Caatinga domain, and we believe that this underscores that the Caatinga anuran fauna, in spite of the vegetation type considered, will generally be similar, using similar behavioral strategies, with sharp behavioral flexibility and heavy reliance on rains.